Analytical comparison of optical code-division multiple-access systems with and without a successive interference cancellation scheme using modified prime-sequence codes - Eltaif, Tawfig; Shalaby, Hossam M. H.; Shaari, Sahbudin; Hamarsheh, Mohammad M. N. (SPIE-SOC PHOTOPTICAL INSTRUMENTATION ENGINEERS, 2008)
We analyzed direct-sequence code-division multiple-access system using a successive interference cancellation (SIC) scheme. Modified prime-sequence codes are utilized as signature sequences, and the performance measure studied in this paper takes into account the the effect of imperfect interference cancellation. The basic principle of the SIC scheme is to subtract the strongest received signals from the original signal one by one till all users have been detected and demodulated. In this analysis we have compared optical code-division multiple-access systems with and without the cancellation scheme, and it is shown that the SIC scheme with -20-dBm effective power can suppress multiple-access interference better than the system without cancellation. (C) 2008 Society of Photo-Optical Instrumentation Engineers.